Pengaruh Arsitektur Terhadap Kecerdasan Emosional Pada Anak Usia Sekolah Dasar - wahyu kusuma tn; Vijar Galax Putra Jagat Paryoko (Universitas Muhammadiyah Palembang, 2026)
Bullying is also called bullying, which is still one of the problems affecting children in Indonesia with serious impacts on both the perpetrators and the victims. Some of this happens to elementary school children, who should be at an age where they develop their emotional intelligence and empathy that can be influenced by their environment. To solve this problem, an approach consisting of various steps is needed. By prioritizing aspects such as sensory experience, architecture has the power to deeply influence emotions and behavior. This method does not only use punishment but also acts proactively to encourage better behavior. This study aims to find the influence of architecture in forming a child-friendly environment in terms of psychology. A case study at MI Khoirul Huda indicates that designing a learning environment that accommodates aspects of safety, comfort, and sensory stimulation makes a significant contribution to the formation of emotional intelligence in children. However, there are still several design elements that need to be optimized so that the quality of the space truly supports the process of psychological and emotional development of students as a whole. This study uses a qualitative method with primary data collected through observation techniques on the study object of the MI Khoirul Huda Education building. The results of this study indicate that architectural design can have a good or bad impact on the emotional intelligence of elementary school children.